Estimates for distributions of components of mixtures with varying concentrations - Maiboroda, R. E. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For the data of sampling from a mixture of several components with varying concentrations, we construct nonparametric estimates for the distributions of components and determine the rank correlation coefficient. We prove the consistency of the rank coefficient and the efficiency of the estimates of distributions.